Synthesis, cytotoxicity and in vitro antileishmanial activity of naphthothiazoles - de Toledo, Juliano S.; Junior, Paulo E. S.; Manfrim, Viviane; Pinzan, Camila F.; de Araujo, Alexandre S. [UNESP]; Cruz, Angela K.; Emery, Flavio S. (Wiley, 2013)
The leishmaniasis is a spectral disease caused by the protozoan Leishmania spp., which threatens millions of people worldwide. Current treatments exhibit high toxicity, and there is no vaccine available. The need for new lead compounds with leishmanicidal activity is urgent. Considering that many lead leishmanicidal compounds contain a quinoidal scaffold and the thiazole heterocyclic ring is found in a number of antimicrobial drugs, we proposed a hybridization approach to generate a diverse set of semi-synthetic heterocycles with antileishmanial activity. We found that almost all synthesized compounds demonstrated potent activity against promastigotes of Leishmania (Viannia) braziliensis and reduced the survival index of Leishmania amastigotes in mammalian macrophages. Furthermore, the compounds were not cytotoxic to macrophages at fivefold higher concentrations than the EC50 for promastigotes. All molecules fulfilled Lipinski's Rule of Five, which predicts efficient orally absorption and permeation through biological membranes, the in silico pharmacokinetic profile confirmed these characteristics. The potent and selective activity of semi-synthetic naphthothiazoles against promastigotes and amastigotes reveals that the 2-amino-naphthothiazole ring may represent a scaffold for the design of compounds with leishmanicidal properties and encourage the development of drug formulation and new compounds for further studies in vivo. © 2013 John Wiley & Sons A/S.
Keywords: Fragment embedment; Leishmania braziliensis; Leishmaniasis; Naphthothiazoles; Neglected tropical disease; antileishmanial agent; naphthothiazole derivative; unclassified drug; amastigote; animal cell; antiprotozoal activity; computer model; controlled study; dose response; drug absorption; drug bioavailability; drug cytotoxicity; drug penetration; drug synthesis; in vitro study; macrophage; mammal cell; membrane permeability; molecular hybridization; mouse; nonhuman; parasite survival; priority journal; promastigote